Participation of Mitochondrial Metabolism in Photorespiration : Reconstituted System of Peroxisomes and Mitochondria from Spinach Leaves - Raghavendra, Agepati S. (American Society of Plant Physiologists, 1998)
In this study the interplay of mitochondria and peroxisomes in photorespiration was simulated in a reconstituted system of isolated mitochondria and peroxisomes from spinach (Spinacia oleracea L.) leaves. The mitochondria oxidizing glycine produced serine, which was reduced in the peroxisomes to glycerate. The required reducing equivalents were provided by the mitochondria via the malate-oxaloacetate (OAA) shuttle, in which OAA was reduced in the mitochondrial matrix by NADH generated during glycine oxidation. The rate of peroxisomal glycerate formation, as compared with peroxisomal protein, resembled the corresponding rate required during leaf photosynthesis under ambient conditions. When the reconstituted system produced glycerate at this rate, the malate-to-OAA ratio was in equilibrium with a ratio of NADH/NAD of 8.8 × 10(−3). This low ratio is in the same range as the ratio of NADH/NAD in the cytosol of mesophyll cells of intact illuminated spinach leaves, as we had estimated earlier. This result demonstrates that in the photorespiratory cycle a transfer of redox equivalents from the mitochondria to peroxisomes, as postulated from separate experiments with isolated mitochondria and peroxisomes, can indeed operate under conditions of the very low reductive state of the NADH/NAD system prevailing in the cytosol of mesophyll cells in a leaf during photosynthesis.